Responsabilización por medio del control social estudio de caso veeduría ciudadana aplicada a un gobierno autónomo descentralizado del Ecuador - Peláez Moreno, Lenin Ernesto (2014)
Research plays an important topic for the democratization of the state and its management, reviewing citizen oversight mechanism how state accountability instrument. For this purpose, the methodology used for the research includes: a solid theoretical framework, a historical review, a conceptual and policy analysis; framework in which a case study was based on documentary analysis, interviews with citizens and providers both officers and authorities of the autonomous decentralized government and the Council of Citizen Participation and Social Control, have been actors in a process of oversight is addressed a local government.